FAMILY PREPARATION FOR A FUTURE WITHOUT STUNTING - Suhaid, Dewi Novitasari; Wardani, Dyah Woro Kartiko Kusumo (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Stunting is a condition in which children under five years of age fail to achieve optimal growth as a result of chronic inadequate nutritional intake. As a consequence, their height is significantly below the average for their age group. This condition negatively affects both physical and cognitive development, increases the risk of chronic diseases later in life, and ultimately reduces the quality of a nation’s human resources. In Indonesia, stunting remains a major public health concern, influenced by multiple factors including maternal nutritional status, maternal height, limited access to adequate antenatal care (ANC), low birth weight (LBW), and short birth intervals. Adequate maternal nutrition is particularly crucial, as it has a direct impact on fetal growth and development. On July 7, 2025, pregnant women and women of reproductive age in RW 07, Tanah Tinggi, Johar Baru District, participated in a health education program aimed to strengthen family knowledge about stunting, so it can be prevented in children both now and in the future. The activity consisted of a pre-test assessment, followed by the distribution of educational topics covering the definition, prevalence, causes, consequences, and preventive strategies related to stunting. Additional topics addressed maternal nutrition, danger signs in pregnancy, and risk factors that may compromise fetal development. A post-test was administered afterward to evaluate the improvement in participants’ knowledge. The evaluation demonstrated a substantial increase in knowledge. The average score improved from 5.4 on the pre-test to 9.6 on the post-test. These findings indicate that health education is effective in....